Magnetically tunable bandpass filter of teraherz radiation - Kochnev, Zahar S. (Russian physics journal)
A magnetically tunable bandpass filter of terahertz radiation is created and investigated. The filter is a cell with a magnetic fluid and a system of inductance coils made in the form of Helmholtz rings. The magnetic fluid consists of automotive synthetic engine oil and 5BDSR alloy microparticles with a mixed amorphouscrystalline structure. When a cell is placed between the inductance coils and under the action of an external magnetic field, the microparticles are oriented along the magnetic field vector, forming periodic filamentous structures. The filter is controlled by changing the magnitude of the magnetic induction. Eighteen samples of similar bandpass filters were prepared and studied, differing in the properties of the magnetic fluid (concentration and size of magnetic particles). The presented results are useful for creating bandpass magnetically controlled terahertz radiation filters with the required parameters